CREATING AN EFFECTIVE LEARNING ENVIRONMENT AT SCHOOL: INNOVATIVE APPROACHES AND THE ROLE OF THE TEACHER - Ozoda Xudoynazarovna, Qosimova; Muharram Shodiyor Qizi, Turdialiyeva (PT. Antis International Publisher, 2024)
Objective: This study aims to develop an effective learning environment in schools by integrating innovative pedagogical methods, fostering social and emotional growth, and emphasizing a personalized approach to address students' diverse needs. Methods: Modern educational technologies, including online platforms and mobile applications, were employed to enhance interactive learning. Activities such as brainstorming, group work, and project-based tasks encouraged critical thinking and creativity. Teachers adopted personalized approaches to nurture student development while fostering an inclusive atmosphere. Results: The findings indicate that a learning environment grounded in trust, respect, and active engagement significantly enhances students' academic and personal growth. Key factors include the integration of advanced pedagogical methods, emotional support, and personalized teaching. These strategies increased students' motivation, collaboration, and social responsibility, ultimately improving education quality. Novelty: This study highlights the critical role of teachers in transforming classrooms into spaces that balance academic achievement with emotional and social development. By combining innovative methods and inclusive practices, the research underscores a holistic approach to modern education that prepares students not only for academic success but also for societal contributions.